A New Paradigm for Water Resource Governance in Indonesia : Reflecting on Constitutional Court Decision Number 85/PUU-XI/2013 Through the Narrative of Jasser Auda's Maqashid Syariah - Tohari, Ilham; Rohman, Baitur; Toriqirrama, Faby (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2025)
This study examines water resource management in Indonesia following the annulment of the Water Resources Law by Constitutional Court Decision No. 85/PUU-XI/2013, which mandated that water governance prioritize the greatest prosperity of the people. Despite the subsequent enactment of Law No. 17/2019, persistent issues of corporate industrialization, exploitation, and privatization of water sources threaten citizens' fundamental right to water and ecological sustainability. The paper adopts Jasser Auda’s contemporary Maqashid al-Shariah with its system approach as an alternative analytical framework. Auda's methodology shifts the maqasid focus from classical preservation to construction, development, and the fulfillment of human rights (hifdz al-huquq al-insan), employing six interconnected features, including a hierarchical structure. The analysis explicitly places the fulfillment of the people's rights to water within Auda's General Maqasid (Maqasid al-‘Ammah). This classification underscores the urgent need for water access as a fundamental human necessity, requiring a social and public dimension of governance that transcends individual interests.